Barley: a translational model for adaptation to climate change. Issue 3 (21st January 2015) - Dawson, Ian K.; Russell, Joanne; Powell, Wayne; Steffenson, Brian; Thomas, William T. B.; Waugh, Robbie
Summary: Barley ( Hordeum vulgare ssp. vulgare ) is an excellent model for understanding agricultural responses to climate change. Its initial domestication over 10 millennia ago and subsequent wide migration provide striking evidence of adaptation to different environments, agro‐ecologies and uses. A bottleneck in the selection of modern varieties has resulted in a reduction in total genetic diversity and a loss of specific alleles relevant to climate‐smart agriculture. However, extensive and well‐curated collections of landraces, wild barley accessions ( H. vulgare ssp. spontaneum ) and other Hordeum species exist and are important new allele sources. A wide range of genomic and analytical tools have entered the public domain for exploring and capturing this variation, and specialized populations, mutant stocks and transgenics facilitate the connection between genetic diversity and heritable phenotypes. These lay the biological, technological and informational foundations for developing climate‐resilient crops tailored to specific environments that are supported by extensive environmental and geographical databases, new methods for climate modelling and trait/environment association analyses, and decentralized participatory improvement methods. Case studies of important climate‐related traits and their constituent genes – including examples that are indicative of the complexities involved in designing appropriate responses – are presented, and key developments for the future highlighted. Contents Summary 913 I. Introduction 913 II. Barley resources for climate change interventions 915 III. Predictions for barley production and genetic resources based on environmental modelling 917 IV. Examples of important genes and traits under climate change 919 V. Practical approaches for responding to climate change 922 VI. Looking to the future 926 Acknowledgements 927 References 927